Business cycles and economic crises a bibliometric and economic history - Geiger, Niels; Kufenko, Vadim (Routledge, 2019)
Throughout the history of economic thought, interest in business cycles and economic crises tends to rise during times of crises, recessions and depressions. However, the treatment of this topic in the literature has generally been merely anecdotal. This book presents a bibliometric and econometric analysis of the development of business cycle and crises theory and its connection to economic developments, particularly since the early 20th century. The book explores the connection between economic development and the literature, utilising systematic bibliometric and rigorous econometric methods and drawing its data from a wide range of sources. This volume provides quantitative answers to questions which have not previously been subject to a precise and comprehensive empirical analysis. This book will be of great interest to historians of economic thought for its novel treatment of a much-discussed topic, and its well-founded and transparent results
Keywords: Business cycles / History; Financial crises; Bibliometrics; Economics / History